Evolutionary economic geography: reflections from a sustainable tourism perspective. Issue 3 (27th May 2017) - Brouder, Patrick
ABSTRACT: Evolutionary economic geography (EEG) is receiving increasing attention from tourism geographers with over 30 publications explicitly incorporating EEG into tourism between 2011 and 2016. Many of these contributions are conceptual, which is not surprising given the novelty of EEG within economic geography, in general, and tourism, in particular. However, a sizeable number of these are built on detailed case studies, using EEG as an analytical lens rather than as a conceptual point of departure. Thus, many tourism researchers have found that EEG has great potential for understanding change in tourism destinations. In this Research Frontiers paper I critically reflect on this early research of EEG in tourism geographies from a sustainable development perspective. In the cases presented, EEG offers a fresh understanding of two related challenges in each of two separate aspects of sustainable tourism development. First, pro-growth governance models can be disrupted by engaged local stakeholders in order to make tangible sustainability gains but these gains remain precarious over time as pro-growth governance models prove tenacious in the very long-term. Second, regional institutional legacies hamper new path emergence in two ways – through institutional inertia which keeps the region's focus on past success in other sectors and through the (possibly competing) institutional imperatives of the dominant and emerging tourism sub-sectors or sub-regions. These challenges are illustrated through two complementary Canadian cases drawn from the extant literature – the mass tourism destination of Niagara and the resort community of Whistler. I highlight how a sustainable tourism perspective can also help to critique EEG theory and empirics in line with other recent political economy critiques in economic geography. I conclude that sustainable tourism, at its best, is an established reflexive lens which will help to develop, validate, and challenge aspects of EEG theory within tourism studies, in particular, and economic geography, in general.